Influence of internal communication on the organizational climate of a local educational management unit in Peru - Curilla, Sayuri; Morales, José; Poma, Wesley; Vicente-Ramos, Wagner (Business: Theory and Practice, 2023)
The objective of this research is to determine the influence of internal communication on the organizational climate. The method used in this research is the deductive inferential scientific method, for which the type and level of applied and explanatory research were used respectively. The study sample was made up of women (45%) and men (65%), with an age range between 23 years and over, who were the object of study, with a total of 305 workers. The results that were obtained based on the reliability and validity of the measurement scales, where they specify that p < 0.05, that is, that 12 of the 15 hypotheses are accepted in the proposed correlation between internal communication and organizational climate factors, Among them interpersonal relationships, which generates assertiveness among workers, management styles, which implies increasing employee satisfaction, remuneration, which consists of the importance of knowing how to recognize the work of workers. Finally, the collective values, which encourages them to do a proper job and get involved. In conclusion, internal communication is essential to strengthen the organizational climate factors mentioned above. This ensures a good work environment in order to achieve improvements at the hierarchical and organizational level.